UMKM berbasis ekonomi hijau syariah: Menuju pembangunan berkelanjutan dengan dukungan lembaga filantropi Islam - Syamsuddin, Syamsuddin; Nuriana, Mutia Azizah; Abbas, Ngatmin (Alkasb: Journal of Islamic Economics, 2024)
The concept of a Sharia green economy emerges as an innovative approach that integrates Islamic economic principles with green economy concepts. In the Indonesian context, where Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the national economy, exploring the potential implementation of a Sharia green economy in this sector becomes highly relevant. However, there remains a gap in understanding how these principles can be operationalized in Micro, Small, and Medium Enterprises (MSME) business practices. This research aims to explore the relevance and potential implementation of the Sharia green economy in developing MSME productivity in Indonesia, specifically focusing on the strategic role of philanthropic institutions in supporting this transition. This study employs a descriptive method with a literature review approach. The analysis will be conducted on various literature sources such as journal articles, books, research reports, and policy documents relevant to the Sharia green economy, MSMEs, and Islamic philanthropy. This approach will allow for a comprehensive synthesis of existing knowledge and identification of gaps in the literature. Expected results: The research is expected to produce a conceptual framework illustrating how Sharia green economy principles can be operationalized in the MSME context, as well as a theoretical model of the strategic role of philanthropic institutions in supporting this transition. The research findings are also expected to provide directions for future empirical research and policy recommendations for creating an ecosystem that promotes the development of sharia green economy-based MSMEs in Indonesia.